How section 90 of the Constitution makes cannabis law reform less likely in Australia. (December 2020) - Keyzer, Patrick
Cannabis law reform is unlikely in Australia because section 90 of the Constitution gives the exclusive power to tax goods to the Commonwealth, yet it is the states and territories that have the power to decriminalise use. What incentive does a state have to decriminalise cannabis if they cannot tax it? This article summarises the High Court's s 90 jurisprudence. It also briefly explores the question of whether the states or territories could impose a levy on cannabis as a 'fee for services rendered' in the event that a user accesses state health services for cannabis-related health conditions.